Impact of crystal polymorphism on the systemic bioavailability of rifaximin, an antibiotic acting locally in the gastrointestinal tract, in healthy volunteers - Blandizzi C; Viscomi GC; Scarpignato C (Dove Medical Press, 2014)
Corrado Blandizzi,1 Giuseppe Claudio Viscomi,2 Carmelo Scarpignato31Division of Pharmacology and Chemotherapy, Department of Clinical and Experimental Medicine, University of Pisa, Pisa, 2Research and Development Division, Alfa Wassermann SpA, Bologna, 3Clinical Pharmacology and Digestive Pathophysiology Unit, Department of Clinical and Experimental Medicine, University of Parma, Parma, Italy Background: Rifaximin is an antibiotic, acting locally in the gastrointestinal tract, which may exist in different crystal as well as amorphous forms. The current marketed rifaximin formulation contains polymorph alpha, the systemic bioavailability of which is very limited. This study compared the pharmacokinetics of this formulation with those of the amorphous form.Methods: Amorphous rifaximin was specifically prepared for the study and formulated as the marketed product. Two doses (200 mg and 400 mg) of both formulations were given to two groups of 12 healthy volunteers of either sex according to a single-blind, randomized, two-treatment, single-dose, two-period, cross-over design. Plasma and urine samples were collected at preset times (for 24 hours or 48 hours, respectively) after dosing, and assayed for rifaximin concentrations by high-performance liquid chromatography-mass spectrometry.Results: For both dose levels, peak plasma concentration, area under the concentration-time curve, and cumulative urinary excretion were significantly higher after administration of amorphous rifaximin than rifaximin-α. Ninety percent confidence intervals for peak plasma concentration, area under the concentration-time curve, and urinary excretion ratios were largely outside the upper limit of the accepted (0.80–1.25) range, indicating higher systemic bioavailability of the amorphous rifaximin. The few adverse events recorded were not serious and not related to the study medications.Conclusion: Rifaximin-α, a crystal polymorph, does differ from the amorphous form, the latter being systemically more bioavailable. In this regard, care must be taken when using – as a medicinal product – a formulation containing even small amounts of amorphous form, which may alter the peculiar pharmacologic properties of this poorly absorbed antibiotic. Keywords: rifaximin, crystal polymorphism, systemic bioavailability, gastrointestinal tract